Tumor‐infiltrating lymphocytes in breast FNA biopsy cytology: A predictor of tumor‐infiltrating lymphocytes in histologic evaluation. Issue 5 (7th February 2022) - Odate, Toru; Le, Minh‐Khang; Kawai, Masataka; Kubota, Mizuki; Yamaguchi, Yohei; Kondo, Tetsuo
Abstract : Background: Tumor‐infiltrating lymphocytes (TILs) are associated with various clinicopathological features. Using cytologic specimens for assessing TILs remains to be established. This retrospective study aimed to establish a practical method to assess TILs in cytologic samples. Methods: The authors found 1101 breast fine‐needle aspiration biopsy (FNAB) cytology samples in their hospital, and 214 of them met the inclusion criteria. The TILs score was evaluated using histologic slides, and breast cancers were divided into 2 groups: low‐ (<60%) and high‐TILs (≥60%). Training and validation tests composed of 50 breast cancer samples each were constructed. A cytologic TILs (cTILs) score was introduced to evaluate lymphocytes in FNAB cytology and it was compared with histologically evaluated TILs. The cTILs score was calculated by subtracting the number of neutrophils from the number of lymphocytes surrounding the tumor cells. Results: In the training test, a 2‐tier system with low‐ and high‐TILs groups showed a large area under the curve (AUC) (0.943; 95% confidence interval [CI], 0.84‐0.99). A cTILs score cutoff value of >8 had 87.5% sensitivity and 90.5% specificity. In the validation test, the AUC was 0.79 (95% CI, 0.6‐0.93) whereas sensitivity and specificity were 57% and 89.5%, respectively. When small tumors <0.5 cm were excluded, the AUC improved to 0.93 (95% CI, 0.83‐1.0), and sensitivity and specificity were 80% and 88.5%, respectively. Conclusions: The cTILs scoring system had acceptable reproducibility and concordance with TILs on histologic samples for tumors ≥0.5 cm. Cytologic evaluation can potentially substitute for histologic evaluation of TILs. Abstract : This study shows a good concordance between tumor‐infiltrating lymphocytes (TILs) evaluated by histology and fine‐needle aspiration biopsy (FNAB) cytology. FNAB cytology can potentially substitute for histological assessment of TILs.